Positive community responses to an arts-health program designed to tackle diabetes and kidney disease in remote Aboriginal communities in Australia: a qualitative study - Craig Sinclair; Annette Stokes; Christine Jeffries‐Stokes; Jeanne Daly (Elsevier, 2016)
Abstract Objective: The Western Desert Kidney Health Project (WDKHP) is an innovative clinical screening, arts-health and community development program, staffed by Aboriginal health workers. The WDKHP is aimed at prevention and early detection, improving the chance of better management of kidney disease among people in 10 predominantly Aboriginal communities in rural Western Australia. This paper aimed to understand community responses to the WDKHP in three of these communities. Methods: Interviews were undertaken with 26 Aboriginal people living in three remote communities. Community responses were analysed with attention to the social organisation of participants in each community and a focus on the perspectives of key groups, identified here as 'Community Leaders', 'Homelanders', 'Refuge Seekers' and 'Dislocated'. Results: Participants from all groups reported that the WDKHP was highly acceptable, and an effective means of drawing attention to the need for prevention, early detection and management of diabetes and kidney disease. The integration of Aboriginal health workers to explain the project contributed to the high rates of participation in clinical screening. Conclusions: Outreach clinical services can be an appropriate method of engaging people in remote communities in addressing diabetes and kidney disease. Implications: The remote community setting can act as an 'enabler' of healthy lifestyle for Aboriginal people, particularly when augmented by well‐designed outreach programs.